Sustainable heritage: analysis of bulding's thermal behaviour - Ramos, A.T.V.F. (2010)
The energy consumption of buildings has presented a steady growth in face of the global energy consumption. This fact is related to a variety of factors, including the increased demand for comfort by the inhabitants, the low quality of construction of buildings and their inadequacy to the climatic and environmental context in which they are included. Reversing this tendency includes the necessary intervention in the built environment, promoting the attainment of comfort through interventions that respect the principles of sustainability in construction, namely in resource consumption over the building’s life cycle. Energy rehabilitation can be accomplished by enhancing the envelope’s thermal protection using strategies in terms of i) strengthening insulation in the opaque envelope; ii) strengthening insulation of the glazing and iii) control of solar gains. The use of passive solar systems and the improvement of energy systems are other approaches for improving the thermal performance of dwellings. This study examines the constructive characteristics and the pathologies found in approximately 700 buildings located in Coimbra’s downtown (“Baixa”), the historic sector of the city. From this analysis it was possible to assess the present-day performance of these buildings, attending to the existing code and the application of DesignBuilder software, and to define the desired levels of performance resulting from rehabilitation procedures. The definition of these levels allows the superintendence of the process of intervention, taking into account the solutions to adopt with regard to the principles of sustainability.